Succinea peruviana (Gastropoda) in the diet of the Lomas lizard Microlophus tigris (Sauria) from the Lachay National Reserve, Peru - Pérez Z., José (2008)
We report the snail Succinea peruviana in the diet of the Lomas lizard Microlophus tigris, which inhabit the mesohabitat from the formation forested of Lomas in the Lachay National Reserve. This is the first report of snails in the diet of Peruvian coastal desert lizards.